Are things starting to change in the labor market for library and information science graduates? - Moreiro-González, José-Antonio (Anuario ThinkEPI, 2016)
The evolution of the labor market for information professionals in 2015 is analyzed with a focus on the graduates of library and information science (LIS). For those who were qualified from 2009 through 2014, statistical data from the Spanish Statistics National Institute (INE) report on employment were used. Also the labor market evolution between 2009 and 2015 for information professionals with university degrees was analyzed using data from the Spanish State Public Employment Service (SEPE). Finally, information was obtained through a questionnaire sent to LIS graduates in the 2014-15 academic year. The results are shown in tables and figures along with comments that complete the situation analysis. The three sources of information show signs of a troubled but improving labor market.